The Asperkid's (secret) Book of Social Rules : the handbook of not-so-obvious social guidelines for tweens and teens with Asperger syndrome - Cook, Jennifer, 1975-; Bojanowski, Brian (London : Jessica Kingsley, 2012)
Ideal for all 10-17 year olds with Asperger syndrome, this book provides inside information on over 30 social rules in bite-sizes chunks that older children will enjoy, understand, and most importantly use daily to navigate the mysterious world around them.
Includes bibliographical references and filmography.
Keywords: Asperger's syndrome -- Juvenile literature; Asperger's syndrome -- Social aspects -- Juvenile literature; Asperger's syndrome -- Patients -- Life skills guides -- Juvenile literature; Teenage Non-Fiction.; Personal and Social Issues